2018
DOI: 10.1186/s12916-018-1123-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of longitudinal alcohol consumption trajectories with coronary heart disease: a meta-analysis of six cohort studies using individual participant data

Abstract: BackgroundStudies have shown that alcohol intake trajectories differ in their associations with biomarkers of cardiovascular functioning, but it remains unclear if they also differ in their relationship to actual coronary heart disease (CHD) incidence. Using multiple longitudinal cohort studies, we evaluated the association between long-term alcohol consumption trajectories and CHD.MethodsData were drawn from six cohorts (five British and one French). The combined analytic sample comprised 35,132 individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 58 publications
1
34
1
Order By: Relevance
“…It has been reported that the dose of alcohol is associated with the biological effect on diabetes and cardiovascular diseases [30]. Thus, it is believed that lower alcohol intake may be beneficial to maintaining metabolic health and reducing cardiovascular disease risk [31]. No statistically significant association was found between cigarette smoking and metabolic status in normal weight individuals.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the dose of alcohol is associated with the biological effect on diabetes and cardiovascular diseases [30]. Thus, it is believed that lower alcohol intake may be beneficial to maintaining metabolic health and reducing cardiovascular disease risk [31]. No statistically significant association was found between cigarette smoking and metabolic status in normal weight individuals.…”
Section: Discussionmentioning
confidence: 98%
“…When an individual reported low-risk or heavy drinking on an equal number of occasions, participants were assigned to the unstable heavy drinking group. Participants were permitted one missing alcohol value during follow-up (O'Neill et al, 2018).…”
Section: Measuring Alcohol Consumptionmentioning
confidence: 99%
“…Studies have shown that alcohol exerts protective effects against risk factors for atherosclerosis, such as hypertension, a high body mass index (BMI), and an increased level of high-density lipoprotein cholesterol (HDL-c); improves endothelial function; increases insulin sensitivity; and reduces fasting insulin resistance. 3,4 Many studies have focused on the formation of atherosclerotic plaques, but few studies have focused on changes in artery diameter. An increased coronary artery diameter may be associated with a reduced severity of CHD.…”
Section: Introductionmentioning
confidence: 99%